On the Inhibition Mechanism of Glutathione Transferase P1 by Piperlongumine. Insight From Theory - Prejanò, Mario; Marino, Tiziana; Russo, Nino (Frontiers in Chemistry, 2018)
Piperlongumine (PL) is an anticancer compound whose activity is related to the inhibition of human glutathione transferase of pi class (GSTP1) overexpressed in cancerous tumors and implicated in the metabolism of electrophilic compounds. In the present work, the inhibition mechanism of hydrolyzed piperlongumine (hPL) has been investigated employing QM and QM/MM levels of theory. The potential energy surfaces (PESs) underline the contributions of Tyr residue close to G site in the catalytic pocket of the enzyme. The proposed mechanism occurs through a one-step process represented by the nucleophilic addition of the glutathione thiol to electrophilic species giving rise to the simultaneous C-S and H-C bonds formation. Both the used methods give barrier heights (19.8 and 21.5 kcal mol−1 at QM/MM and QM, respectively) close to that experimentally measured for the C-S bond formations (23.8 kcal mol−1).